Gunshot Fractures of the Forearm: A Multicenter Evaluation. Issue 10 (October 2021) - Veltre, David R.; Tornetta, Paul; Krause, Peter; George, Mary P.; Vallier, Heather; Nguyen, Mai P.; Reich, Michael S.; Cannada, Lisa; Eng, Michael; Miller, Anna N.; Goodwin, Alexandra; Mir, Hassan R.; et al.
Abstract : Objectives: To evaluate a large series of open fractures of the forearm after gunshot wounds (GSWs) to determine complication rates and factors that may lead to infection, nonunion, or compartment syndrome. Design: Multicenter retrospective review. Setting: Nine Level 1 Trauma Centers. Patients/Participants: One hundred sixty-eight patients had 198 radius and ulna fractures due to firearm injuries. All patients were adults, had a fracture due to a firearm injury, and at least 1-year clinical follow-up or follow-up until union. The average follow-up was 831 days. Intervention: Most patients (91%) received antibiotics. Formal irrigation and debridement in the operating room was performed in 75% of cases along with either internal fixation (75%), external fixation (6%), or I&D without fixation (19%). Main Outcome Measures: Complications including neurovascular injuries, compartment syndrome, infection, and nonunion. Results: Twenty-one percent of patients had arterial injuries, and 40% had nerve injuries. Nine patients (5%) developed compartment syndrome. Seventeen patients (10%) developed infections, all in comminuted or segmental fractures. Antibiotics were not associated with a decreased risk of infection. Infections in the ulna were more common in fractures with retained bullet fragments and bone loss. Twenty patients (12%) developed a nonunion. Nonunions were associated with high velocity firearms and bone defect size. Conclusions: Open fractures of the forearm from GSWs are serious injuries that carry high rates of nonunion and infection. Fractures with significant bone defects are at an increased risk of nonunion and should be treated with stable fixation and proper soft-tissue handling. Ulna fractures are at a particularly high risk for deep infection and septic nonunion and should be treated aggressively. Forearm fractures from GSWs should be followed until union to identify long-term complications. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.